Parameter Ekologis Sebagai Dasar Pengelolaan Bivalvia di Ekosistem Lamun di Kecamatan Ponelo Kepulauan Kabupaten Gorontalo Utara - Riskawati Nento; Hasim Hasim; Ramli Ramli (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2019)
Ponelo Islands is an important area to be developed with the economic potential of fisheries and marine resources. This research was conducted in May-September 2019 aimed to find out Ecological Parameters as the Basis of Bivalvia Management in Seagrass Ecosystems. The sampling method is done by using the method used in determining the observation point is the linear quadratic transect method with sampling bivalves determined intentionally with a systematic perpendicular direction using a transect measuring 1x1 m. All bivalves contained in transects / quadrants are counted and identified. The sampling locations were divided into 4 (four) stations, namely Station I (Otiola Village), Station II (Ponelo Village), Station III (Malambe Village), and Station IV (Tihengo Village). Observations at the study site found several types of seagrass ecosystems including Enhalus acoroides, Halodule pinifolia, Thalassia hemprichii, and Cymodocea raotundata. Furthermore, 8 (eight) types of bivalves were found which were divided into 4 (four) stations in Ponelo Islands, namely Isognomon isognomum, Pinna muricata, Semele crenulata, Tellina virgata, Trachycardium subrugosum, Spondylus tenellus, Tapes sulcarius, Anadara pilula. The highest abundance index value is Tellina virgata found in Otiola Village with a value of 77.78%. The dominance index value for the highest is in Ponelo Village with a value of 0.88 in the high category. diversity index (D') with a value of 0.63 found in the medium category Malambe village. Keywords: Bivalvia, Seagrass, Abundance, Dominance, Diversity